استشراق:اسلامی مطالعات کے محرکات و مقاصد: Orientalism: Motives and Objectives of the Study of Islam (Al-Qamar, 2018)
This article is an attempt to find out whether orientalism is really a weapon of the West against Islam? It brings out the facts that the Christians sacrificed millions of lives in the Crusades; their great leaders were killed in these wars but they could not suppress the Muslims. Due to constant blows from the Muslims, West resorted to other tactics to weaken the Muslims instead of armed conflict. They convinced that the strength of Muslims lay in the teachings of Islam and the only way to weaken them was to portrait Islam and Prophet of Islam in such a way that Muslims would feel ashamed to be called Muslims. They put down the sword, picked up the pen and started maligning Islam and Prophet of Islam in dramas, films, cartoons and books. Orientalism is a form of this war-like strategy of the West.
Keywords: Orientalism; Islam; West; sword; pen